Features of National Mentality in Ukrainian Musical Folklore - Yakymchuk, Olena (Resital: Jurnal Seni Pertunjukan, 2025)
The article explores the manifestation of the Ukrainian national mentality in the genres of musical folklore, focusing on dumas, schedrivkas, and lyrical songs. The study considers the national mentality as a historically formed system of cognitive and emotional dispositions, culturally coded and transmitted through collective practices such as folklore. Applying a multidisciplinary methodology that combines elements of cultural studies, ethnomusicology, and semiotic analysis, the study identified specific features of the Ukrainian worldview, which are reflected in the symbolic structures and stylistic features of the folk song, namely: individualism, emotional expressiveness, respect for nature and family, and democratic ethos. This study adopts a semiotic approach, which considers folklore as a complex system of cultural signs that convey collective meanings and values. The semiotic analysis focuses on the symbolic structure of folk songs, i.e., binary oppositions, archetypal images, ritual motifs, which interpret the Ukrainian national mentality. The study comprises 100 Ukrainian folk songs, including shchedrivkas, dumas, and lyrical songs, collected from different regions of Ukraine, with a particular emphasis on the Central and Western regions of Ukraine. Moreover, it is established that the dual cultural heritage of the agrarian and Cossack traditions forms the ambivalent structure of the Ukrainian mentality. By analyzing the textual and musical characteristics of key folklore genres, the article shows how musical folklore functions as a means of preserving and transmitting national identity and collective memory. Ukrainian musical folklore reproduces key features of the Ukrainian character, such as emotionality, the desire for freedom, democratic ideals, and a deep connection to nature. Thus, it stipulates reinterpretation of the role of folklore in the formation of cultural identity in postcolonial societies.